Highly efficient phenothiazine 5, 5-dioxide-based hole transport materials for planar perovskite solar cells with a PCE exceeding 20%. Issue 16 (4th April 2019) - Ding, Xingdong; Chen, Cheng; Sun, Linghao; Li, Hongping; Chen, Hong; Su, Jie; Li, Huaming; Li, Henan; Xu, Li; Cheng, Ming
Abstract : Two novel highly efficient and low-cost phenothiazine 5, 5-dioxide core building block based hole transport materials are reported, achieving a power conversion efficiency as high as 20.2%. Abstract : Two novel phenothiazine 5, 5-dioxide (PDO) core building block-based hole transport materials (HTMs), termedPDO1 andPDO2, were designed and synthesized. The introduction of a sulfuryl group in a core unit can deeply influence the energy levels and charge carrier mobilities of relative HTMs. The combined suitable energy level alignment, higher hole mobility and conductivity, as well as highly efficient hole transfer ofPDO2 enable the perovskite solar cell (PSC) to achieve an impressive power conversion efficiency (PCE) of 20.2% and good stability when aged under ambient conditions. These results demonstrate the potential versatility of the PDO building block for further development of cost-effective and highly efficient HTMs for PSCs.